Genetic diversity of improved varieties of intraspecific (O. sativa and O. glaberrima) and interspecific (O. sativa × O. glaberrima) rice - Bah, S.; Labuschagne, Maryke T.; Merwe, R. van der (Springer, 2018)
Information on genotype diversity and interrelationships is essential for germplasm management, crop improvement and seed production. In this study the diversity of a collection of 36 rice accessions comprising of Oryza sativa L., O. glaberrima Steud. and interspecific rice (O. sativa × O. glaberrima) was assessed using 24 agro-morphological and 27 microsatellite markers. The collection was composed mainly of improved cultivars and a few landraces which are adapted to the upland ecology in West Africa. The average Shannon–Weaver diversity index value (H′) was 0.23. The highest diversity was found in O. sativa group Indica (H′ = 0.32), and the lowest (H′ = 0.18) in O. glaberrima. Interspecific rice had intermediate diversity. There were 321 alleles with an average of 11.9 alleles per locus and an average major allele frequency of 0.29 per locus. The average gene diversity value was 0.81 and polymorphism information content was 0.80 per locus. Diversity indices for interspecific rice were intermediate between O. sativa and O. glaberrima, but closer to O. sativa group Japonica. Accessions comprised of two populations which corresponded to O. sativa group Indica and O. sativa group Japonica. Interspecific rice accessions were dispersed between the two groups.